INO Annual Symposium 2020. Quantum for Renaissance - Roati, Giacomo (Il Colle di Galileo, 2021)
The INO Annual Symposium 2020 was a unique occasion for discussing the role of the Institute in the emerging fields of quantum simulation/computing, photonics, sensing and communication, which represent some of the fundamental pillars of the recently launched European Quantum Flagship.